Implementation of Inaportnet Information Technology and Service Performance on User Satisfaction - Prasadja Ricardianto; Dedeh Suryani; Honny Fiva Akira Sembiring; Erni Pratiwi Perwitasari; Tri Mulyani Setyowati; Sri Mulyono; Devi Marlita (AIBPM Publisher, 2022)
The purpose of this study is to know and analyze implementation of Inaportnet Information Technology and service performance on user satisfaction at Tanjung Priok Port. The Implementation of Inaportnet at a port is aimed at improving ship and cargo services at the port so as to enhance the competitiveness of Indonesian ports. The study uses a quantitative method with path analysis. The number of research samples is as many as 62 port service user. The result of the hypothetical test on the research shows the information technology system it is expected that the system can assist the activity processes of a port and reduce the high cost in the port sector, and through Information Technology it can monitor the port activities which still need improvement